(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to examine the relationship between IT Capability at the Digital Workplace, Dynamic Innovation Capability, and Dynamic Digital Workplace Policy on Employee Performance and their subsequent effect on Organizational Performance. Using a Structural Equation Modeling (SEM) approach, the analysis reveals that all hypothesized relationships are statistically significant. The results indicate that IT capability significantly enhances employee performance, suggesting that strong digital infrastructure and technological competence enable employees to work more efficiently and adapt to digital transformation. Similarly, dynamic innovation capability fosters creativity and problem-solving abilities among employees, while adaptive digital workplace policies encourage flexibility and productivity. Furthermore, employee performance shows a strong and positive influence on organizational performance, demonstrating that improved individual performance contributes to better overall organizational outcomes. The mediation test confirms that employee performance significantly mediates the relationship between IT capability and organizational performance, emphasizing that technological capability drives organizational success primarily through its impact on human performance. Overall, this study highlights the strategic importance of integrating digital capability, innovation, and workplace policies to enhance both employee and organizational performance in the digital era.